Biology and Management of Goosegrass (Eleusine indica (L.) Gaertn.) in Tomato, Pepper, Cucurbits, and Strawberry - Nathan S. Boyd; Kiran Fnu; Chris Marble; Shawn Steed; Andrew W. MacRae (EDIS)
This revised 4-page fact sheet gives a brief description of the biology and management of goosegrass, a common annual turf and horticultural weed found throughout Florida that grows well in compact, wet soils and superficially resembles crabgrasses. Written by Nathan S. Boyd, Kiran Fnu, Chris Marble, Shawn Steed, and Andrew W. MacRae, and published by the Horticultural Sciences Department, August 2016.